2020
DOI: 10.1088/1757-899x/830/4/042063
|View full text |Cite
|
Sign up to set email alerts
|

Women in mechanical engineering at vocational high school

Abstract: The purpose of this research was to knowing why in recent years there has been an increase in the number of students who choose to continue their education to a technical vocational high school. The low involvement of women in the field of engineering technology and mathematics caused by a gender gap, the influence of negative stereotypes, culture, and character where the engineering field is more intended for men who are masculine and not by women. The research was conducted by interviewing participants who w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Academic interests played a significant role in the motivations, career decisions, and decision-making processes of the participants. Almost all participants indicated that their high school experiences and coursework changed their understanding of engineering, particularly the issue of gender bias and the social stigma toward female engineering and STEM learners (Balta et al, 2017;Firdaus et al, 2020). The participants argued that engineering skills and knowledge could be applied to many real-life practices and experiences, which encouraged them to continue to study this subject as their university major.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Academic interests played a significant role in the motivations, career decisions, and decision-making processes of the participants. Almost all participants indicated that their high school experiences and coursework changed their understanding of engineering, particularly the issue of gender bias and the social stigma toward female engineering and STEM learners (Balta et al, 2017;Firdaus et al, 2020). The participants argued that engineering skills and knowledge could be applied to many real-life practices and experiences, which encouraged them to continue to study this subject as their university major.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Therefore, an understanding of the connection between students' sense-making processes for their university major and their career choices and desires is important for guiding the design of human resources planning and engineering programmes. In accordance with the guidelines of the Social Cognitive Career Theory (Dos Santos, 2020;Lent et al, 1994;Lent & Brown, 1996), many participants believed that their perspectives as female users could help them use their gender as an advantage for merging and improving results, outcomes, and designs in mechanical engineering, such as for vehicles and robots (Firdaus et al, 2020). More important, many expressed their interest and long-term career development goals in this field, regardless of the field's social stereotypes and social stigma (Wu et al, 2020).…”
Section: Potential For Career Development and Opportunities In The Future Robot Industrymentioning
confidence: 94%
“…Moreover, due to a retirement wave, contemporary women need to work to fill the gap of human resource shortages. Particularly in mechanical engineering, the demands for female professionals are very high in response to various elements and factors of human resource management (Firdaus et al, 2020). However, the current statistics on engineering feature little to attract and motivate women to join the field of mechanical engineering.…”
Section: Statement Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation